O direito ao trabalho por parte das pessoas com deficiência: o acesso ao cargo público e seu efetivo exercício - Oliveira, Milena Sousa de (2017)
The study of the rights of persons with disabilities reveals the true battle fought by the minorities in Brazil. According to the last survey performed by the Brazilian Institute of Geography and Statistics (IBGE), in 2010, there are over 45 million Brazilians, about 23.9% of the national population, with some form of disability (sensory, cognitive, intellectual, physical, etc.). Among these, 61.1% of the persons with disabilities above 15 years of age have been deprived of proper primary education. Furthermore, only about 54.8% of the persons with disabilities have a formal occupation - a number at least 10% higher than the one observed for persons without any disabilities in the same age span (between 15 and 69 years of age). This shows that, in spite of the recent advances in the legislature, there is still a lot to be done in order materialize the access of the persons with disabilities to their most basic social rights and, through these, attain their much desired social inclusion. In this sense, the access to work emerges as one of the most powerful vectors for obtaining social inclusion, being the productive exercise of citizenship. Being born with a disability, or developing it over one's life, should not be a discriminating factor authorizing the restriction of the person with disability to his right to work. The Brazilian Federal Constitution, based on the values of democracy, equality, citzenship and justice, promotes the first affirmative action in pro of the persons with disabilities by, in its article 37, clause VIII, securing that a minimum number of the available jobs in the government be secured for this group of people. The access to a public office involves not only being hired for the job but also having the conditions necessary to effectively perform the duties associated with the acquired position. This, however, seems to be the newest setback faced, at least in the public service, by the persons with disabilities on their quest for materializing their right to work, and by it find in their productive force real human dignity. The national and international legislature offer several possible solutions for this problem, however, there are still a multitude of gaps the be filled so that the right to work can be effectively beheld by many of the persons with disabilities.